AMENDMENT OF COPYRIGHT LAW FROM COMPLAINT OFFENCE TO ORDINARY OFFENCE IN REVIEW ACCORDING TO JARIMAH HUDUD - Siti Mawar; Lena Marliani (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2018)
Changes in Copyright Law has existed, but the classification of copyright offences is still classified as a complaint offence. The amendment of copyright law No. 6 of 1982 with UUHC No. 7 of 1987 resulted in a change in the type of classification of copyright offences from complaint offences into ordinary offences. This study aims to explain the basis of the issuance of Act No. 7 of 1987 so that there is a change in the classification of offences changed from complaint offences into ordinary offences related to criminal law policy and to know and explain how the legal protection of copyright after the change in the classification of offences, as well as the view of Islamic law into jarimah ḥudud. Data analysis is done in the form of library research, namely by descriptive analysis method, which is a method of describing, describing things related to the problem written and researched. The results showed that the consideration of the issuance of UUHC No. 7 Year 1987 based on the dictum weighing that is because there are still many copyright infringements during the classified as a complaint offence. Changes in the type of classification of offences in the UUHC due to pressure from outside countries on the Indonesian government to change the provisions of the UUHC because the Act in force is perceived as unable to overcome the violations and copyright crimes that occur. While in Islamic criminal law the act of piracy may be subject to punishment. Piracy is classified into jarimah ḥudud with punishment in the form of cutting hands if it has reached the nisab. In theqiasan method, the punishment for piracy is equated with the punishment for theft (Sariqah). Whereas in positive law, the penalty is imprisonment for a maximum of five years or a fine of Rp.500,000.00 in accordance with Article 72 of Law No. 19 of 2002 concerning Copyright Protection.